Optimisation and modification of TiO2 nanorods towards a highly efficient interfacial layer for uniformly CU2O deposition in heterojunction solar cell applications - Ahmad, Norazlina (2021)
The deficiency of successful heterojunction solar cell development detains the future implementation of oxide-based photovoltaic devices. In the group of semiconducting compounds, titanium dioxide (TiO2) which has superior properties in solar cell development, and copper (I) oxide (Cu2O) is the best candidate that serves as an absorber layer, owing to its excellent optical properties. In this work, TiO2 with a well-aligned nanorods structure and high adhesion was synthesized on fluorinedoped tin oxide (FTO) substrate by hydrothermal method. The incorporation of Cu2O